Effective HRM through Digitalization: Preliminary Study in Hospitality Industry - Chaddha, Stuti (Journal of Advanced Research in Information Technology, Systems and Management; Vol 3 No 2 (2019): Journal of Advanced Research in Information Technology, Systems & Management, 2021)
This study is on the essentialness of digitalization, the change and its impact on human resources, their ability and execution. The study was undertaken in 3 hotels situated in Delhi NCR area. This investigation is grounded on the interviews. It incorporates distinctive parameters for example, understanding the turnaround time, on boarding handling, acclimatizing the on-going training & development exercises, the level of empowerment and different verticals of the human resource. This has given an understanding with respect to how and where digitalization can be utilized and how it can help in accelerating the on-going exercises. To have a clearer guide the interview was led on Level 1 and Level 2 employees for knowing their observation with respect to the HR processes. Further, this investigation helped in understanding the root exercises that are to be done by HR, in order to make a balance in the workplace of Pullman-Novotel.